Chemotaxonomic studies of mesembrine-type alkaloids in Sceletium plant species - Patnala, Srinivas; Kanfer, Isadore (South African Journal of Science, 2013)
Complementary medicines containing the succulent herb Sceletium are being sold without information regarding their phytochemical contents, which is essential for the quality control of medicines. Furthermore, several different Sceletium species exist and little has been reported on the alkaloidal identities and contents of the various species. We therefore conducted phytochemical investigations on six selected Sceletium specimens, identified on the basis of their venation pattern as either ‘emarcidum’ or ‘tortuosum’ type. The tortuosum type consisted of S. tortuosum, S. expansum and S. strictum, whereas the emarcidum type consisted of S. emarcidum, S. exalatum and S. rigidum. Analysis was conducted by high-performance liquid chromatography with UV and alkaloids were identified by online mass spectroscopy.